2011
DOI: 10.5665/sleep.1122
|View full text |Cite
|
Sign up to set email alerts
|

Does Sleep Duration Predict Metabolic Risk in Obese Adolescents Attending Tertiary Services? A Cross-Sectional Study

Abstract: Contrary to expectations, sleep duration was not associated with metabolic outcomes, and showed limited associations with lipid profiles. Although inadequate sleep may affect other areas of functioning, it appears premature to expect that lengthening sleep will improve BMI or metabolic outcomes in clinical samples of obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 56 publications
(60 reference statements)
4
29
0
Order By: Relevance
“…35 The other found that short sleep was related to high fasting glucose in obese but not nonobese children. 33 Five studies reported no associations; 24;26;3638 all of these were studies of the metabolic syndrome and 1 was from a sample in a weight management clinic. In sum, the majority of the evidence suggests that sleep characteristics are related to indices of glucose and insulin metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…35 The other found that short sleep was related to high fasting glucose in obese but not nonobese children. 33 Five studies reported no associations; 24;26;3638 all of these were studies of the metabolic syndrome and 1 was from a sample in a weight management clinic. In sum, the majority of the evidence suggests that sleep characteristics are related to indices of glucose and insulin metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of these sleep measures were associated with the MetS-score in our cross-sectional analysis. Another study using accelerometers in obese adolescents found no association between sleep duration and the prevalence of metabolic syndrome [38]. Other studies using accelerometer-determined sleep duration and quality found a negative association with blood pressure [39] or no association [40], whereas evidence for a link between short sleep duration and insulin resistance [41][45] or waist circumference [46] is more evident.…”
Section: Discussionmentioning
confidence: 97%
“…In a cross-sectional study of 133 obese adolescents, neither objective (actigraph, Mini-Motionlogger; Ambulatory Monitoring, Inc, Ardsley, New York) nor subjective (parent and self-report) sleep duration were associated with individual metabolic outcomes nor did any measures of sleep duration differ in the presence versus absence of metabolic syndrome. 59 The authors noted the unexpected finding that short sleep duration was associated with lower triglyceride and increased HDL-C levels. Our use of a continuous cMetScore rather than evaluation of its individual components may, in part, explain the differences in findings.…”
Section: Discussionmentioning
confidence: 99%